Jaminan Hak Asasi Manusia Bagi Pekerja Rumah Tangga Melalui Perjanjian Kerja - Alia Farhana; Rasji Rasji (LPPM Universitas Ekasakti Padang, 2023)
One of the issues faced by domestic workers (PRT) is the lack of attention to Human Rights Assurance (HAM). This problem is evident from the fact that the Manpower Law No. 13 of 2003 does not cover domestic workers, resulting in them not receiving the protection they should have as laborers. The relationship between domestic workers and employers is informal, so there is no legal regulation governing this relationship. The aim of this research is to explore how Human Rights Assurance for Domestic Workers can be realized through Employment Agreements in Surabaya. This study uses a qualitative approach and is conducted in the West Surabaya region. The research subjects involve part-time and non-residential domestic workers. Data is collected through literature review and in-depth interviews. The results show that employment agreements for domestic workers are often neglected, and legal protection for the rights and obligations of domestic workers still needs to be strengthened. This is intended to ensure the basic rights of domestic workers and to ensure equal opportunities and treatment without discrimination, in order to improve the welfare of domestic workers and their families.